(untitled) (Global Journal of Human-Social Science, 2014)
The Universe is created in common algorithm The law and phenomenon natural have very simple explanation The micro and macro universes have one genuine origin In other words the world has one absolutely phenomenon of emergence display and affection beyond forties a time impression We don t know what electron and core atom is We don t know neither what kind elementary particle composed the electron proton and neutron Only we suppose that it is very small particle What structure of this elementary particles